The Incidence Rate of Helminthiasis in The Digestive Tract of Dairy Cattle in The Partnership of PT. Greenfields Indonesia - Wenny Nur Azizah; Dony Chrismanto; Sri Pantja Madyawati; Hana Eliyani (Journal of Applied Veterinary Science And Technology, 2020)
Background: One of the partnerships of PT. Greenfields Indonesia is located on the slopes of Mount Kawi, precisely in Pijiombo, Ngadirenggo Village, Wlingi District, Blitar Regency. The tropical situation in this area is very humid and has high rainfall. It causes dairy cattle to be infected with helminths. Therefore, observations of the incidence rate of gastrointestinal helminthiasis in dairy cattle are needed. Purpose: To determine the prevalence of gastrointestinal helminths in dairy cattle in the partnership of PT. Greenfields Indonesia. Method: Fecal samples from 36 dairy cattle were collected and examined using native, sedimentation, and flotation techniques. Result: Indicated that the prevalence of gastrointestinal helminths in the dairy cattle was about 66,66%. There were 24 dairy cattle positively and 12 cattle negatively. Helminth species found included class Nematoda (Haemonchus contortus, Oesophagostomum radiatum, Bunostomum phlebotomum, Mecistocirrus digitatus, and Gaigeria pachyscelis) and Cestoda (Moniezia expansa). Conclusion: The incidence rate of helminthiasis was quite high dairy cattle in the partnership of PT. Greenfields Indonesia.